2020
DOI: 10.3390/su12187735
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media on Tourists’ Behavior: An Empirical Analysis of Millennials from the Czech Republic

Abstract: Due to the emergence of Web 2.0 and consequently the increased use of social media, this study aims to explore the role of social media in changing the behavior of tourists and the choice of a destination. Despite the massive popularity of social media, the studies with a comprehensive set of driving constructs along with indicators of social media regarding the changing behavior of tourists are lacking in the literature. Therefore, framed by the theory of planned behavior (TPB), the present study fulfills thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 99 publications
2
44
0
1
Order By: Relevance
“…This finding is also supported by Cheng et al ( 2017 2020), Chung and Khoo (2015) and No and Kim (2015) revealed that social media plays an essential role in communicating, interact and influence the tourist's behaviour and tourism development. However, the study by Javed et al (2020) indicated social media as a source of tourism promotion illustrated a non-significant relationship with the prediction of tourists' behavioural intention and actual behaviour. A reliability test is essential in research to evaluate the item's internal consistency used in the survey instrument.…”
Section: Resultsmentioning
confidence: 91%
“…This finding is also supported by Cheng et al ( 2017 2020), Chung and Khoo (2015) and No and Kim (2015) revealed that social media plays an essential role in communicating, interact and influence the tourist's behaviour and tourism development. However, the study by Javed et al (2020) indicated social media as a source of tourism promotion illustrated a non-significant relationship with the prediction of tourists' behavioural intention and actual behaviour. A reliability test is essential in research to evaluate the item's internal consistency used in the survey instrument.…”
Section: Resultsmentioning
confidence: 91%
“…The virtual community can increase the contact frequency of friends in reality by holding various online and offline activities, and the higher the frequency of their information exchange, the user is likely to have a sense of belonging to the virtual community and increase satisfaction in the harvesting of friendship and knowledge. 61 , 62 Besides, through comments and feedback from users of virtual communities, companies can quickly understand their problems and improve their qualities, thereby strengthen users’ loyalty to the virtual communities.…”
Section: Research Contributionmentioning
confidence: 99%
“…The prior section showed the decisive impact of the Internet and social media on traveler planning and usefulness during a vacation. The Theory of Planned Behavior (TPB) (Ajzen, 1985;Javed et al, 2020) helps explain the underlying motivation behind social media's impact on behavior. This theory suggests a linkage between behavioral intention and actual conduct.…”
Section: Impact Of the Internet And Social Media On Tourism In Rural Areasmentioning
confidence: 99%
“…This theory suggests a linkage between behavioral intention and actual conduct. Using TPB, Javed et al (2020) found that the Internet and social media were essential in helping tourists find and then plan vacations to more re-mote rural areas. A fascinating insight from their research was the importance of videos in influencing traveler behaviors to visit these areas.…”
Section: Impact Of the Internet And Social Media On Tourism In Rural Areasmentioning
confidence: 99%